Thermodynamic performance limits of the organic Rankine cycle: Working fluid parameterization based on corresponding states modeling. (1st August 2020) - Yang, Fufang; Yang, Fubin; Chu, Qingfu; Liu, Qiang; Yang, Zhen; Duan, Yuanyuan
Graphical abstract: Highlights: Defined and determined the thermodynamic performance limits of ORC. Parameterized working fluid properties based on corresponding states modeling. Revealed how these limits are affected by property parameters. Presented a few remarks on working fluid selection based on property parameters. Abstract: The organic Rankine cycle (ORC) is a promising technology in low-and-medium temperature energy utilization. As power cycles operate between hot and cold heat sources, the universal behavior of working fluids presents upper limits in addition to the first and second laws on the system thermodynamic performance. Knowing these limits provides insights on what the highest possible performance of a given technology is, what the optimal working fluids are, and how the behavior of working fluids affects the system thermodynamic performance. In the present work, based on the principle of corresponding states, working fluid thermodynamic properties are captured and parameterized using 5 property parameters, which are usually available from chemical manufacturers and theoretical estimations, and thus are available in the early stages of system design. Hypothetical working fluids are defined in a continuous thermodynamic space that comprises these parameters. Multi-objective optimizations are performed in the thermodynamic space for the property parameters rather than ORC operation parameters. Optimal hypothetical working fluids are targeted under various given operation conditions and assumptions, representing the thermodynamic performance limits, beyond which further improvements are forbidden by the universal behavior of thermodynamic properties. Impacts of each property parameter on the ORC thermodynamic performance are analyzed. Furthermore, comparisons with the Carnot limit and current working fluids are presented. This work presents a methodology to define the thermodynamic performance limits, to target the desired characteristics in working fluids, and to reveal the mechanism of how system thermodynamic performance changes with certain working fluid property parameters.